184k views
0 votes
F(x) = 2x^2 - 5x + 3
g(x) = 4x^2 - 12x + 9
find (f/g) (x)

F(x) = 2x^2 - 5x + 3 g(x) = 4x^2 - 12x + 9 find (f/g) (x)-example-1

2 Answers

3 votes

Answer:

16x^4 - 80x^3 + 138x^2 - 95x + 24.

f(x) = 2x^2 - 5x + 3.

Explanation:

User Ealeon
by
4.8k points
5 votes

Answer:

D

Explanation:

Factorise the numerator and denominator

2x² - 5x + 3 = (x - 1)(2x - 3)

4x² - 12x + 9 = (2x - 3)²

Hence


(f(x))/(g(x))

=
(2x^2-5x+3)/(4x^2-12x+9)

=
((x-1)(2x-3))/((2x-3)^2)

Cancel the factor (2x - 3) on the numerator/denominator leaving


(x-1)/(2x-3) → D

User Stephan Ewen
by
4.8k points